2020
DOI: 10.1098/rsos.191715
|View full text |Cite
|
Sign up to set email alerts
|

Older adults detect happy facial expressions less rapidly

Abstract: Previous experimental psychology studies based on visual search paradigms have reported that young adults detect emotional facial expressions more rapidly than emotionally neutral expressions. However, it remains unclear whether this holds in older adults. We investigated this by comparing the abilities of young and older adults to detect emotional and neutral facial expressions while controlling the visual properties of faces presented (termed anti-expressions) in a visual search task. Both age groups detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…On the other hand (Holland et al, 2018), point out that both (AM) and (AJ) do not exhibit major differences when correctly identifying emotions through facial expressions when using dynamic materials, a concept contradicted by (Beer, 2015), who mention that no matter the type of material observed, dynamic or static (AM) show worse results performing this task compared to their younger peers, (Murphy, 2010), on the other hand points out that (AM) have more problems identifying anger than (AJ). (West et al, 2012), explain that the (AM) have greater difficulty recognising the emotions of fear, anger and to a greater extent sadness, sharing the idea with other authors cited above that these people recognise disgust more easily, this study concludes by pointing out that both the (AM) and the (AJ) do not show major differences when it comes to assertively recognising the emotions happiness and surprise, an idea refuted by (Saito et al, 2020), who report that the (AM) do exhibit greater difficulties and make more mistakes than the (AJ) in identifying happiness.…”
Section: Resultssupporting
confidence: 75%
“…On the other hand (Holland et al, 2018), point out that both (AM) and (AJ) do not exhibit major differences when correctly identifying emotions through facial expressions when using dynamic materials, a concept contradicted by (Beer, 2015), who mention that no matter the type of material observed, dynamic or static (AM) show worse results performing this task compared to their younger peers, (Murphy, 2010), on the other hand points out that (AM) have more problems identifying anger than (AJ). (West et al, 2012), explain that the (AM) have greater difficulty recognising the emotions of fear, anger and to a greater extent sadness, sharing the idea with other authors cited above that these people recognise disgust more easily, this study concludes by pointing out that both the (AM) and the (AJ) do not show major differences when it comes to assertively recognising the emotions happiness and surprise, an idea refuted by (Saito et al, 2020), who report that the (AM) do exhibit greater difficulties and make more mistakes than the (AJ) in identifying happiness.…”
Section: Resultssupporting
confidence: 75%
“…Experimental psychology studies of healthy participants have demonstrated that using the visual-search paradigm, emotional expressions were detected faster than emotionally neutral expressions 3 13 . For instance, Williams et al 5 instructed participants to search for target faces in arrays of distractor faces and tested the effects of emotional expressions on search behavior.…”
Section: Introductionmentioning
confidence: 99%
“… Suzuki and Akiyama (2013) reported that when neutral expressions were presented momentarily followed by labeling of the presented expressions, the hit rate of joyful expressions decreased and false positives increased in elderly participants. On the other hand, Saito et al (2020) reported that immediate detection of joyful expressions by the visual search paradigm is less likely to occur in elderly participants. In the present study, seven different facial expressions were presented at once suggesting that happiness was relatively easy to identify.…”
Section: Discussionmentioning
confidence: 99%